Analysis of the Evacuation Route Effectiveness Based on the Hotel’s Visitor Evacuation Speed (Case Study: Grand Kanaya Hotel, Medan) - N. Vinky Rahman; Lenita Aulia Sinaga (International Journal of Architecture and Urbanism, 2019)
The territory of Indonesia has geographical, geological, hierarchical and demographic conditions that enable disasters or emergencies, whether caused by natural or non-natural factors. When an emergency occurs, evacuation must be carried out as quickly and effectively as possible to minimize losses. Evacuation Emergency conditions are things that need to be considered by every building manager. However, until now buildings are still often found that are operating but have not met the requirements of building function worthy certificates. The hotel building is one of the buildings that need to be considered is the emergency response system and its evacuation route. The hotel building is a vertical residential building that has many users and activities, so it requires an optimal evacuation route. This study aims to analyze the effectiveness of evacuation routes in hotel buildings and recommend proper evacuation routes for a hotel building. A descriptive study was conducted to determine the existing conditions and simulations using Rockwell Arena software to determine the visitor's evacuation speed in hotel buildings. The results of the research and simulation of Rockwell Arena software indicate that the evacuation path in hotel buildings has not been sufficient so that design recommendations are needed to improve the effectiveness of evacuation routes. This research can be used as a reference and consideration for finding out the problems that exist on the evacuation routes in hotel buildings.